Communication : principles for a lifetime - Beebe, Steven A., 1950-; Beebe, Susan J.; Ivy, Diana K. (Harlow: Pearson, 2022)
"The purpose of this book is to document this claim by presenting fundamental principles of human communication that enhance the quality of our communication with others as well as the quality of our own lives. Most students who read this book will take only one communication course during their entire college career"--
Includes index.
Keywords: Communication